2017
DOI: 10.1002/2211-5463.12279
|View full text |Cite
|
Sign up to set email alerts
|

High‐density lipoprotein protects cardiomyocytes from oxidative stress via the PI3K/mTOR signaling pathway

Abstract: Low levels of plasma high‐density lipoprotein ( HDL ) cholesterol are associated with an increased risk of heart failure, regardless of the presence or absence of coronary artery disease. However, the direct effects of HDL on failing myocardium have not been fully elucidated. We found that HDL treatment resulted in improved cell viability in H9c2 cardiomyocytes under oxidative stress. This cardioprotective effect of HDL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…In addition, several studies have identified mTOR as an important regulator of cardiac adaptation because its overexpression is protective in pressure-overloaded mouse hearts 47 , 48 ) and its conditional knockout in murine heart causes cardiac dysfunction 49 ) . We demonstrated that HDL activated downstream effectors of mTOR signaling, which played anti-apoptotic roles under oxidative stress, may contribute to cardioprotection 45 ) .…”
Section: Hdl Protects Cardiomyocytes Against Oxidative Stressmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition, several studies have identified mTOR as an important regulator of cardiac adaptation because its overexpression is protective in pressure-overloaded mouse hearts 47 , 48 ) and its conditional knockout in murine heart causes cardiac dysfunction 49 ) . We demonstrated that HDL activated downstream effectors of mTOR signaling, which played anti-apoptotic roles under oxidative stress, may contribute to cardioprotection 45 ) .…”
Section: Hdl Protects Cardiomyocytes Against Oxidative Stressmentioning
confidence: 89%
“…We recently reported that HDL treatment improved cardiomyocyte viability under oxidative stress through the phosphatidylinositol 3-kinase (PI3K)/mammalian target of rapamycin (mTOR) signaling pathway 45 ) . mTOR belongs to the PI3K-related kinase family and critically regulates protein synthesis, cell survival, growth, and proliferation 46 ) .…”
Section: Hdl Protects Cardiomyocytes Against Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, higher TG level can be viewed as a remote circulating marker of failure in buffering excessive TG from saturated VAT capacity. Conversely, recent molecular evidence has also indicated that HDL can resist oxidative stress and protect cardiomyocytes 30 by serving as a scavenger to reverse imbalanced lipid/energy metabolism and likely provides key beneficial regulatory effects via neurohormonal inactivation 31 . In aggregate, we speculated that both TG and HDL may therefore serve as markers or play essential roles in regulating myocardial homeostasis and functions through their remote effects.…”
Section: Discussionmentioning
confidence: 87%
“…FADS1, INSIG1, and LDLR are regulated through SREBP2 pathway likely as a result of the reduction of the cellular cholesterol content. HDL particles may also affect on basic mediators regulating not only lipid biosynthesis but other anabolic processes (Nagao et al, 2017) as well as maintenance and repair reactions (Kimura et al, 2010). Target of rapamycin (mTOR), central mediator of anabolic processes including activation of SREBPs with further lipid biosynthesis, is involved in the induction of trained immunity (Cheng et al, 2014).…”
Section: Monocyte Activatability and Lipid Profilementioning
confidence: 99%